Neuroscience and Hifdz Maqasid Sharia as an Innovation in the Development of Moral Education in Islam - Suruddin, Suruddin; Misno, Misno; Mulyani, Oom; Mulyadi, Enday; As-Salafiyah, Aisyah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
Moral and character education faces great challenges in today's modern society. Moral education for children is often hampered by their increasingly modern and complex environment. This research uses a qualitative approach with a library research method. The data used to explore, analyse, and interpret this research comes from primary data sources, namely books on neuroscience, education, hifdz al-'Aql, and secondary data from scientific journals, articles, documents, and relevant digital sources. The purpose of this research is to integrate neuroscience methods with hifdz al-'Aql in children's moral education with the aim of developing better character building strategies. The findings of this study show that the combination of neuroscience and the principle of hifdz al-'Aql can provide a comprehensive approach to moral education, by understanding that the moral learning process does not only depend on the delivery of values, but also on the development of children's brains and cognitive abilities. This research confirms, this interdisciplinary use has the potential to produce an educational framework that is more flexible and responsive to the challenges of the times, providing teachers with more efficient tools to prepare a generation that is more in line with its nature.